Ethnic identity and national self-determination notes on the moro people's revolution in the Philippines - San Juan, Epifanio, Jr. (Iloilo City UP Visayas, 2007)
"The Moro people's struggle in the Philippines for national self-determination has placed under critical interrogation the hallowed theories of cultural pluralism, liberal tolerance, and multiculturalism that continue to legitimize the domination of diverse ethnic groups under elite control in contemporary Filipino society. Bourgeois political norms and laws have led since colonial times to the severe dispossession, exclusion, and utter impoverishment of the Moro people as a distinct historical community united under Islamic faith and an uninterrupted history of preserving its relative autonomy through various modes of anticolonial resistance. Since the Spanish (1621-1898) and American colonial period (1899-1946) up to the present Arroyo government's neocolonial polity subservient to U.S. hegemony, the Moro people have suffered national, class and religious oppression. The Moro insurgents are labeled "terrorists" and stigmatized daily by the media, schools, Christian churches, and international business. It is the obligation of Filipino Marxists and progressive organizations around the world to recognize the Moro people's right to self-determination and offer solidarity by a preliminary critique of neoliberal ideology, including sectarian ultra-leftism that apologizes for, and foments overtly and covertly, the genocidal wars currently raging int eh Moro homelands of southern Philippines."
Keywords: Ethnicity -- Southern Philippines; Moro people